2017
DOI: 10.1002/1873-3468.12566
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of EIF4G2 by miR‐379 potentiates the cisplatin chemosensitivity in nonsmall cell lung cancer cells

Abstract: Although microRNAs and EIF4G2 are both known to play pivotal roles in cancer progression, it remains unknown whether these pathways regulate chemosensitivity in a coordinated manner. Here, we show that miR-379 expression is significantly downregulated in chemoresistant nonsmall cell lung cancer (NSCLC) tissues and cells. Manipulation of miR-379 levels could alter the in vitro and in vivo cisplatin (CDDP) resistance in lung cancer (LCa) cells. Mechanistically, miR-379 potentiated LCa chemosensitivity via modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Deregulation of miRNAs has been demonstrated to contribute to cancer progression . In the current study, we paid attention to miR‐379, which has been observed in non‐small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma . Nevertheless, no report on the biological roles of miR‐379 alterations in laryngeal carcinoma has been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deregulation of miRNAs has been demonstrated to contribute to cancer progression . In the current study, we paid attention to miR‐379, which has been observed in non‐small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma . Nevertheless, no report on the biological roles of miR‐379 alterations in laryngeal carcinoma has been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the current study, we paid attention to miR-379, which has been observed in non-small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma. [16][17][18][19] Nevertheless, no report on the biological roles of miR-379 alterations in laryngeal carcinoma has been characterized. We focused on miR-379 as a candidate anti-oncogene in laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor recurrence and metastasis are main causes of death in patients with NSCLC, and chemotherapy drug resistance is one of the key factors leading to recurrence and metastasis of NSCLC [6]. Currently, cisplatin is a major drug used in chemotherapy of NSCLC, and it facilitates cross-linking between heavy metal ions and cell DNA chain through the connection with nuclear protein, ultimately damaging DNA [7,8]. NSCLC cells have high sensitivity to cisplatin at early stages of treatment, but most of the cells become resistant to chemotherapy after several cycles, leading to failure of chemotherapy [9].…”
Section: Introductionmentioning
confidence: 99%